An Optimisation Scheme Based on the Local Interaction Simulation Approach and Lamb Waves for Elastic Property Estimation in Multi-Layered Composites. (2012) - Spencer, A.B.; Worden, K.; Staszewski, W.J.; Rongong, J.A.; Sims, N.D.
Abstract : The paper demonstrates the application of guided ultrasonic waves for estimating material elastic properties in multi-layered composite plates. Two-dimensional Lamb wave propagation is modelled using the Local Interaction Simulation Approach (LISA). The wave responses are then used to estimate relevant material properties. This numerical inverse method is based on an optimisation scheme using a Differential Evolution (DE) algorithm. The method is demonstrated on a simulated seven-layered glass fibre-epoxy composite plate. The results show a good agreement between the exact and reconstructed material properties. Erratum of "An Optimisation Scheme Based on the Local Interaction Simulation Approach and Lamb Waves for Elastic Property Estimation in Multi-Layered Composites" dx.doi.org/10.3233/SAV-2012-0755